会宁胡麻油产地环境及产品特征 Production environment and product characteristic of Huining flaxseed oil - 谢亚萍1,2, 任亮3, 齐向辉3, 张建平1, 王利民1, 李闻娟1, 齐燕妮1, 党照1, 赵玮1, 贾尚军4 XIE Yaping1,2, REN Liang3, QI Xianghui3, ZHANG Jianping1, WANG Limin1, LI Wenjuan1, QI Yanni1, DANG Zhao1, ZHAO Wei1, JIA Shangjun4 (Zhongguo youzhi, 2023)
为提高会宁胡麻油品牌知名度和影响力，探究了地理标志产品会宁胡麻油的产地环境、种植方式及生产管理过程和品质特性。以会宁县17个乡镇的土壤和胡麻油为试验材料，采用国家相关标准对产地环境及胡麻油品质进行分析并采用气相色谱-质谱法对胡麻油风味物质进行分析。结果表明：会宁胡麻油的产地环境和产品安全指标均达到绿色食品标准；会宁胡麻油中α-亚麻酸平均含量为54.24%，不同产地间存在一定差异；会宁胡麻油含有65种风味物质，香味浓郁，其中己醛、正己醇、2-甲基吡嗪、γ-己内酯和3-甲基巴豆腈对会宁胡麻油独特的香味有重要影响。综上，会宁胡麻生长环境好，会宁胡麻油香味浓郁、营养价值高。In order to improve the brand awareness and influence of Huining flaxseed oil, the production environment, cultivation method and production management process, and quality characteristics of Huining flaxseed oil, a geographical indication product, were explored.The soil and flaxseed oil from 17 townships in Huining county were used as test materials, and the production environment and product quality were determined by the relevant national standards, and the flavor compounds of flaxseed oil were determined by GC-MS method.The results showed that the production environment and product safety indicators of Huining flaxseed oil could meet the standards of green food; the average content of α-linolenic acid in Huining flaxseed oil was 54.24%, moreover, there was difference among different townships.Furthermore, the flaxseed oil of Huining contained 65 flavor compounds and had aromatic flavor, of which hexanal, hexyl alcohol, 2-methylpyrazine, γ-caprolactone, and 3-methyl crocetonitrile had important effect on the unique scent of Huining flaxseed oil.In summary, the flaxseed of Huining grows in a good environment and the oil has a rich aroma and high nutritional value.